IMPACT OF TWO-SPOTTED SPIDER MITE (TETRANYCHUS URTICAE KOCH) INFESTATION LEVELS ON GROWTH METRICS AND YIELD OF SUMMER APPLE CULTIVARS - Rahmanov Ahliddin Xabibullayevich (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This study investigates the effects of varying populations of two-spotted spider mites (Tetranychus urticae Koch) on the growth parameters and yield of summer apple cultivars. Field experiments were conducted to measure the impact of mite infestations at different density levels on leaf chlorophyll content, fruit growth, leaf area, and overall yield. Results demonstrated significant negative correlations between mite populations and apple growth metrics. High mite densities severely decreased leaf chlorophyll content, leaf area, and fruit size, subsequently reducing overall yield. Effective mite management strategies are necessary to maintain optimal apple production levels.